2018
DOI: 10.17576/3l-2018-2402-03
|View full text |Cite
|
Sign up to set email alerts
|

A Responsive Pedagogical Initiative for Multimodal Oral Presentation Skills: An Action Research Study

Abstract: Poor oral presentation skills amongst ESL speakers are frequently linked to weakness in general English proficiency. However, the literature has also identified the lack of a systematic and effective pedagogical method to develop students' multimodal oral presentation skills to meet 21 st century communication realities. This paper elucidates the application of a pedagogical initiative for multimodal oral presentations skills, informed by the Sociocultural Theory of Learning created by Vygotsky (1978), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Because of this, they were not able to include the important details that they should include in their speeches, which also led to a lot of stuttering and nonconfident way of speaking that also led to some English grammar mistakes. This information was supported by other researchers because according to Seau, Azman, and Noor's (2018) study, "poor oral presentation skills amongst ESL speakers are frequently linked to weakness in general English proficiency. However, the literature has also identified the lack of a systematic and effective pedagogical method to develop students' multimodal oral presentation skills to meet 21 st century communication realities.…”
Section: Significant Difference Between the Meansupporting
confidence: 56%
See 1 more Smart Citation
“…Because of this, they were not able to include the important details that they should include in their speeches, which also led to a lot of stuttering and nonconfident way of speaking that also led to some English grammar mistakes. This information was supported by other researchers because according to Seau, Azman, and Noor's (2018) study, "poor oral presentation skills amongst ESL speakers are frequently linked to weakness in general English proficiency. However, the literature has also identified the lack of a systematic and effective pedagogical method to develop students' multimodal oral presentation skills to meet 21 st century communication realities.…”
Section: Significant Difference Between the Meansupporting
confidence: 56%
“…However, the literature has also identified the lack of a systematic and effective pedagogical method to develop students' multimodal oral presentation skills to meet 21 st century communication realities. (Seau, Azman, and Noor, 2018).…”
Section: Significant Difference Between the Meanmentioning
confidence: 99%
“…In this process, the learner is the creator of knowledge and meaning (Weegar & Pacis, 2012) and the centre of all learning activities (Gray, 1997). Previous studies have shown that sociocultural theory is of great significance for guiding second language teaching, especially second language oral teaching (Kyuchukov et al, 2018;Seau et al, 2018). The three core tenets of sociocultural theory are specified below.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Communication criteria, which are called exemplary, include being always ready and appropriately respond to the audience by adjusting the tone of voice, depth, speed and position when presenting. At the time of the presentation, it is necessary to be responsive to the audience, convey information using one's own words that are easy to understand, use the right position on the screen and appear reasonable, without being too flashy (Dolan, 2018;Seau, Azman, & Noor, 2018;Sharif, 2016). In addition, it is also necessary to pay attention to the non-verbal aspects of the presentation such as hand movements and eye contact (Seau et al, 2018;Sharif, 2016).…”
Section: Presentation Skillsmentioning
confidence: 99%